COMPARATIVE EFFECTIVENESS OF MODERN METHODS OF DIFFERENTIAL DIAGNOSIS OF OVARIAN NEOPLASMS - Мария Алексеевна Егунова; Ирина Георгиевна Куценко; Алла Ивановна Дмитриева; Лидия Валентиновна Пикалова; Елена Александровна Кунгурова; Наталья Александровна Василенко (The Publishing House Medicine and Enlightenment, 2018)
The aim of the research - to identify the most informative methods of differential diagnosis of ovarian neoplasms at the preoperative stage. Materials and methods. The study involved 117 patients with ovarian neoplasms. The level of the tumor marker HE-4 was determined in all patients at the preoperative stage in addition to the standard examination. Risk of Malignancy Index (RMI) and Risk of Ovarian Malignancy Algorithm (ROMA) were calculated. Protocols of histological examination were studied after operations. The prognostic value of CA-125, HE-4, RMI and ROMA were calculated. Statistical analysis of the data is carried out. Results. The most informative parameter for the differential diagnosis of benign and malignant ovarian neoplasms at the preoperative stage in the study was the RMI. Tumor marker HE-4 was characterized by the lowest sensitivity with the highest specificity in the differential diagnosis of ovarian neoplasms among the methods studied. The replacement of CA-125 by HE-4 in the RMI calculation formula (calculation of the «modified» malignancy index) led to an increase in the sensitivity and prognostic significance of the method in the differential diagnosis of ovarian neoplasms at the preoperative stage, which requires further study. Conclusion. Taking into account the high prognostic value of RMI and the «modified» ovarian malignancy index, it is recommended to calculate the above indices at the preoperative stage to assess the nature of ovarian neoplasms (benign ormalignant).